La problématisation d’élèves du primaire impliqués dans une démarche d’apprentissage par problème dans une perspective d’enseignement des controverses - Dion-Routhier, Justine; Hamel, Christine (Canadian Journal of Education/Revue canadienne de l’éducation, 2020)
Society faces major changes. Schools have to allow students to develop the competencies necessary to be active citizens (Albe, 2009). Dewey (1910/2004; 1916/1990) emphasizes the benefits of problem-based learning (PBL) where students need to become familiar with social issues. This study aims to document the PBL process based on a controversial issue of elementary school students to understand how they reflect. In a case study approach, students group discussions were analyzed to identify the phase of the reflective thinking (Dewey, 1910/2004) in their inquiry process. We observe that, following an iterative process, students’ reflective thinking becomes more complex. Keywords: problem-based learning, inquiry learning, controversial issue, elementary education